105k views
5 votes
0 = (2x - 3)(x + 1)

2 Answers

4 votes

Answer:

4 1/3

Explanation:

srech it up n internet

User Nextorlg
by
5.2k points
4 votes

Answer:

x = 3/2, x = -1

Explanation:

0 = (2x - 3)(x + 1)

Let's use the zero product property to split this into two equations, 0 = 2x - 3 and 0 = x + 1.

0 = 2x - 3

3 = 2x

x = 3/2

0 = x + 1

-1 = x

The two solutions are x = 3/2 and -1.

User Protocole
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.